2020
DOI: 10.1155/2020/6195050
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Suppressed Tumor Growth through Regulating Fatty Acid Metabolism and Triggering Cell Apoptosis via Targeting FABPs

Abstract: Aim. To further investigate the mechanism behind the antitumor properties of berberine regarding lipid metabolism. Methods. Cell viability, proliferation, and apoptosis assays were performed to determine the antigrowth effects of berberine in vitro. Ectopic xenograft models in Balb/c nude mice were established to determine the antitumor effects of berberine in vivo. Results. Berberine inhibited cell viability and proliferation of MGC803 human gastric cancer cell lines in a time-and dose-dependent manner. Berbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…The metabolism of fats and lipids plays a role in the malignancies of the digestive system and is one of the advantageous mechanisms of the consequences of berberine in the metabolic syndrome. Berberine induces apoptosis in gastric cancer cells through the reduction of fatty acid accumulation and the reduction of FABP expression [138]. Berberine also down-regulates lipogenic enzymes, which are key in colon cancer.…”
Section: Anticancer Activity Of Berberinementioning
confidence: 99%
“…The metabolism of fats and lipids plays a role in the malignancies of the digestive system and is one of the advantageous mechanisms of the consequences of berberine in the metabolic syndrome. Berberine induces apoptosis in gastric cancer cells through the reduction of fatty acid accumulation and the reduction of FABP expression [138]. Berberine also down-regulates lipogenic enzymes, which are key in colon cancer.…”
Section: Anticancer Activity Of Berberinementioning
confidence: 99%
“…This cost is the energy consumed for the utilization of acetyl-CoA and this could be the energy for FAS. In one study, berberines were found to be inhibitors of fatty acid binding proteins—a family of proteins that transport fatty acids across the membranes [ 221 ]. Given this fact, cancer cells appear to be more dependent on external fatty acids than on their own.…”
Section: Atp Production and Oxygen Consumption By The “ β ...mentioning
confidence: 99%
“…The influence on the metabolism of fats and lipids is one of the mechanisms of berberine action in the aforementioned metabolic diseases, but it also seems to be very important in malignancies, especially those of the digestive system. It has been described that berberine can act by inducing apoptosis via reduction of FABP expression and accumulation of fatty acids in gastric cancer [ 93 ] and by downregulation of key lipogenic enzymes in colon cancer. Berberine targets the SREBP-1 cleavage-activating protein-1/sterol receptor element-binding protein-1 (SCAP/SREBP-1) pathway driving lipogenesis, inhibits the pathway and thus results in downregulation of lipogenic enzymes.…”
Section: Anticancer Activity Of Berberinementioning
confidence: 99%